Investigation into the Impact of L-Shaped RC Shear Wall Placement with Openings on the Behavior of Medium-Rise Buildings - Salem Merabti; Salah Bezari; Abdelkadir Aymen Laari; Aboubaker Khachouche (The Journal of Engineering and Exact Sciences)
This article aims to investigate the impact of regular openings in L-shaped reinforced concrete (RC) shear walls located at building corners. A comparison of different buildings and an estimation of the optimal percentage of openings were conducted. To accomplish this, various wall models, with and without openings, underwent numerical simulations using the ETABS program. The research focused on medium-rise ten-story buildings with opening rates of 0%, 15%, 20%, 25%, 30%, and 35% in the X and/or Y direction under high seismic loading conditions (Zone-III) following the Algerian Paraseismic Regulations (RPA 99/version 2003). The findings of this study indicate that openings have a noticeable impact on the overall behavior of buildings and on the shear wall's capacity to withstand earthquakes. However, opening ratios of 20.8%, 30%, and 31.8%, depending on the direction, are considered optimal opening percentages for L-shaped shear walls. These percentages ensure a suitable balance between architectural functionality and the effective structural performance of L-shaped shear walls. Thus, it is important to consider the placement of openings in the design of reinforced concrete structures braced by shear walls.